2012
DOI: 10.1136/heartjnl-2011-301577
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative myocardial necrosis in patients at high cardiovascular risk undergoing elective non-cardiac surgery

Abstract: Objective Cardiovascular complications are important causes of morbidity and mortality in elective non-cardiac surgery. Although difficult to diagnose, perioperative myocardial infarction (MI) remains prognostically important. High-sensitivity troponin T (hs-TnT) assays allow detection of very minor damage to cardiac muscle. These assays are yet to be fully evaluated in the perioperative setting. Our aim was to determine the incidence and predictors of myocardial necrosis in patients at high cardiovascular ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 36 publications
0
52
0
Order By: Relevance
“…A postoperative myocardial necrosis by hsTnT was identified in 22% of patients (a proportion ∼4-fold higher with respect to conventional cTn T assay), even if only 2% of patients experienced clinically apparent AMI. Interestingly, a preoperative hsTnT elevation, detected in 31% of patients, did not predict peri-operative MI [68]. A larger study has reported that hsTnT measured 7 days prior to surgery outperforms conventional risk algorithms, including clinical variables as well as use of natriuretic peptides, in predicting major adverse events (death, AMI, acute heart failure, and cardiac arrest/resuscitation) [69].…”
Section: This Is Not the End: Other Pieces To The Puzzlementioning
confidence: 99%
See 1 more Smart Citation
“…A postoperative myocardial necrosis by hsTnT was identified in 22% of patients (a proportion ∼4-fold higher with respect to conventional cTn T assay), even if only 2% of patients experienced clinically apparent AMI. Interestingly, a preoperative hsTnT elevation, detected in 31% of patients, did not predict peri-operative MI [68]. A larger study has reported that hsTnT measured 7 days prior to surgery outperforms conventional risk algorithms, including clinical variables as well as use of natriuretic peptides, in predicting major adverse events (death, AMI, acute heart failure, and cardiac arrest/resuscitation) [69].…”
Section: This Is Not the End: Other Pieces To The Puzzlementioning
confidence: 99%
“…With the introduction of hsTn, the prognostic value of the marker in these patients has potentially increased according to the capability to detect very minor myocardiocyte damage. A recent study has evaluated if the hsTnT increasing 24 h after surgery could detect peri-operative myocardial damage in patients at high cardiovascular risk undergoing elective non-cardiac surgery [68]. A postoperative myocardial necrosis by hsTnT was identified in 22% of patients (a proportion ∼4-fold higher with respect to conventional cTn T assay), even if only 2% of patients experienced clinically apparent AMI.…”
Section: This Is Not the End: Other Pieces To The Puzzlementioning
confidence: 99%
“…As many as 24% of the patients had a cTnT Ͼ14 ng/L in that study. However, there is mixed evidence regarding whether a preoperatively increased cardiac troponin concentration predicts perioperative myocardial injury (49,50 ). Nonetheless, a preoperatively increased cardiac troponin should prompt a careful search for underlying structural heart disease that may be subclinical.…”
Section: Preoperative Increase In Cardiac Troponinmentioning
confidence: 99%
“…The majority of patients with perioperative myocardial injury do not have classical type 1 MI and go clinically undetected. Imbalance in myocardial oxygen supply/demand causing ischemic injury, e.g., in case of perioperative hypotension tachycardia or fever, is probably the most common cause of perioperative myocardial injury with increase in cardiac troponin (type 2 MI) (49,52,53 ). Patients with preexisting coronary artery disease are at a particular ischemic risk.…”
Section: Myocardial Injury After Noncardiac Surgery (Mins)-perioperatmentioning
confidence: 99%
“…In effect, the peripheral presence of troponin amounts to a cry for help in a population where many cardiac events are silent and thus remain clinically unnoticed. 9,10 Routine postoperative monitoring for this biomarker can thus help identify a population that would ordinarily escape detection until the precipitation of a major clinical event. Second, as the pathophysiology of cardiac events centers around rupture of vulnerable plaque (type-1 MI), supply:demand mismatch (type-2 MI), or both of these phenomena, escalation or institution of important medical risk-reducing treatments (such as aspirin, beta-blockers, or statins), can be established to improve outcomes.…”
Section: Model To Improve Postoperative Cardiac Outcomesmentioning
confidence: 99%